Impact of nitrogen fertilisation strategies on the protein content, gluten composition and rheological properties of wheat for biscuit production - De Santis Michele A.; Giuliani Marcella. M.; Flagella Zina.; Reyneri Amedeo; Blandino Massimo (Field Crops Research, 2020)
The impact of fertilisation strategies on bread-making quality of wheat has been investigated extensively, while only few studies have been carried out on minor supply-chains, such as the biscuit production chain, whose products require a low protein content (< 10.5 %) and weak gluten strength (< 110 J 10−4). The aim of this work was to obtain insight into the effect of N fertilisation strategies on grain yield and quality, by focusing on the changes in the composition of gluten protein and its relationship with dough quality for the biscuit supply-chain. Seven different nitrogen fertilisation strategies, including standard and slow release fertilisers and the combined application of sulphur (S), were compared in relation to the grain yield and quality of two soft wheat cultivars (Artico, Sy Alteo) in a three-years field trial. Canopy development was phenotyped, in terms of NDVI, and Nitrogen Agronomic Efficiency was assessed. Rainfall during grain filling influenced the agronomic and quality performances to a great extent. The effect of N fertilisation was more marked on the P/L and gluten composition than on the grain yield and grain protein content. Genotypes showed similar protein content and W values, and greatly differed for P/L. The gluten protein composition analysis showed that P/L was greatly influenced by the proportion of specific glutenin sub-units, both in HMW-GS (Dx2, Bx7) and in LMW-GS (B- and C-type). Sulphur application, with both standard and slow release fertilisers, contributed to reducing the P/L ratio, with an increase in the C-type LMW-GS. Single application of slow release N fertilisers can be recommended for biscuit making to achieve better qualitative requirements, without compromising the grain yield. In addition, the co-application of sulphur with nitrogen showed an increase in grain yield and modulated glutenin composition (B- and C- type LMW-GSs) and P/L with moderate increase of W.